1998
DOI: 10.1117/12.321614
|View full text |Cite
|
Sign up to set email alerts
|

<title>Mechanisms of laser surface cleaning in liquid media</title>

Abstract: This paper deals with an experimental study on the mechanisms of laser surface cleaning process in a liquid medium.Experiments have been performed with oxides of different compositions irradiated with two different wavelengths: 1064nm, 532nm . Interpretations have been inferred from high speed visualizations, pressure recordings and surface samples analysis. Interesting results on the dynamics of the cavity resulting from ablation and its potential contribution to the cleaning effects have been carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Since 1970s, laser processing in presence of liquid water has been studied, and to date, a series of investigations have been done for water-assisted processes of steam laser cleaning (SLC) [10][11][12], laser shock processing (LSP) [13][14][15] and laser cutting (LC) [16,17]. It was shown that the effect of water in these processes mainly consists of laser energy conversion, materials transport and shock waves induction, as well as cooling the workpiece more effectively and useful chemical reactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1970s, laser processing in presence of liquid water has been studied, and to date, a series of investigations have been done for water-assisted processes of steam laser cleaning (SLC) [10][11][12], laser shock processing (LSP) [13][14][15] and laser cutting (LC) [16,17]. It was shown that the effect of water in these processes mainly consists of laser energy conversion, materials transport and shock waves induction, as well as cooling the workpiece more effectively and useful chemical reactions [8].…”
Section: Introductionmentioning
confidence: 99%